Understanding how Branding Influences Gen Z’s Behavioral Intent with Charitable Food Organizations - Marlee Stollar; Joy N. Rumble; Annie R. Specht (Journal of Applied Communications, 2024)
Food security, also known as having proper access to food to live a healthy life, affects more than 10% of individuals in the United States. Marketing and communications, as well as brand identity, plays a role in how organizations combating food insecurity operate and raise awareness. However, these organizations’ communications are typically not as successful as for-profit corporations, and there is a gap in literature about the effectiveness of these charitable food organizations’ marketing efforts. The purpose of this study was to determine the effect of charitable food organization branding on college students’ support of charitable food organizations—specifically through volunteering, donating behavior, and advocacy efforts. This study used the Theory of Planned Behavior (TPB), color theory, and semiotics to craft treatments similar to social media images from charitable food organizations (CFOs). There were four treatment groups, all with the same verbiage, but all using either color or no color or with an icon versus an image. Findings suggested Treatment 3, the colorful treatment with a picture of two children, had the greatest impact on intent to support CFOs. While some of the other treatment models were significant, none included all significant TPB predictors as with treatment 3. This study’s results indicate that using a post with imagery and color can influence intent to support charitable food organizations. Future research should use qualitative methods to better understand this study and similar studies’ results.
Keywords: Branding; charitable food organizations; food security